Populasi, Serangan, dan Sebaran Hama Hypothenemus hampei pada Kopi Arabika Gayo - Hendrival, Hendrival; Nurdin, Muhammad Yusuf; Usnawiyah, Usnawiyah; Margono, Margono; Ahmadika, Hafizh Mulia (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Hypothenemus hampei (Ferrari) (Coleoptera: Scolytidae) or Coffee Berry Borer (CBB) is the most destructive major pest that causes quantitative and qualitative losses in Arabica coffee. The research aimed to calculate population, attack H. hampei, coffee yield losses, the measure distribution pattern of H. hampei on various Gayo arabica coffee varieties, and the analyze estimated decrease in the production of coffee based on population and attack H. hampei in Gayo arabica coffee. The location chosen as a place of observation and sampling is a smallholder coffee plantation with variations in elevation. Each area is determined by two points of observation and sampling locations. At each sampling location, 80 ripe or red coffees were taken, 80 dark or yellow coffees, and 80 young or green coffees (24 pieces per four branches per tree). The results showed that the population and attack of CBB pests on Gayo 3 varieties are relatively high compared to Gayo 1 and Gayo 2 varieties. The distribution pattern of CBB on all varieties of Gayo Arabica coffee showed an aggregated distribution based on population and attack. The decrease in arabica coffee production has the potential to occur on a variety Gayo 3.